Desmatamentos e suas relações com o clima na região norte mato-grossense : os exemplos de Sinop e Vera - MT - Oliveira, Helana Helen Campos de (2012)
The strong interactions between vegetation and atmosphere may be concluded that deforestation of large areas causing climate change at regional scale. The northern Mato Grosso refuges part of the Cerrado and the Amazon Rainforest, two major biomes of Brazil. In the last decades, large areas of vegetation have been removed due to logging, ranching and grain crops in that field. Trying to evaluate the influence of deforestation and the use and occupation of land in regional climate this research aims to compare the deforestation occurred in the cities of Sinop and Vera, MT, with climatic variations observed in conventional meteorological station over a period of 36 years. The results showed that large areas are deforested and that occurred at the same time trends of temperature rise of the air, reduction in rates of relative humidity and changes in the spatial distribution of rainfall. These facts are indications that deforestation can modify the radiation balance and surface energy between the atmosphere and causing changes in regional climate.